Measurement of adsorption constants of laccase on gold nanoparticles to evaluate the enhancement in enzyme activity of adsorbed laccase. Issue 24 (8th June 2018) - Peixoto de Almeida, Miguel; Quaresma, Pedro; Sousa, Susana; Couto, Cláudia; Gomes, Inês; Krippahl, Ludwig; Franco, Ricardo; Pereira, Eulália
Abstract : Laccase adsorption on gold nanoparticles increases the enzyme activity. Results from adsorption studies were used in a model to assess the activity of adsorbed laccase. Abstract : Adsorption of enzymes to nanoparticles and the mechanisms responsible for enzyme activity modulation of adsorbed enzymes are not well understood. In this work, gold nanoparticles were used for electrostatic adsorption of a plant-derived laccase. Adsorption constants were determined by four independent techniques: dynamic light scattering, electrophoretic light scattering, agarose gel electrophoresis and fluorescence quenching. Stable bionanoconjugates were formed with log  K in the range 6.8–8.9. An increase in enzyme activity was detected, in particular at acidic and close to neutral pH values, a feature that expands the useful pH range of the enzyme. A model for the adsorption was developed, based on geometrical considerations and volume increase data from dynamic light scattering. This indicates that enzymes adsorbed to gold nanoparticles are ca. 9 times more active than the free enzyme.